Newton's rainbow : the revolutionary discoveries of a young scientist - Lasky, Kathryn (Farrar Straus Giroux, 2017)
"A picture-book biography of young Isaac Newton, who "discovered" gravity, developed calculus, and uncovered the secrets of light and color"--